2020
DOI: 10.3390/jcm9020315
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cancer Incidence Following up to 15 Years after Cardiac Catheterization in Infants under One Year between 1980 and 1998—A Single Center Observational Study

Abstract: Objective: To evaluate the incidence of cancer within the first 15 years of life in children who underwent cardiac catheterization under the age of one year. Methods: In this retrospective, single center study, 2770 infants (7.8% with trisomy 21) were studied. All infants underwent cardiac catheterization under one year of age between January 1980 and December 1998. Newly diagnosed cancer in the first 15 years of life was assessed through record linkage to the German Childhood Cancer Registry (GCCR). Cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…There is also an ongoing discussion about the role of low-ionisation radiation and the risk for cancer in CHD patients. 10 , 11 , 29 Unfortunately, in this study, we had no data describing the amount of radiation to which the patients were exposed. One can argue that it is likely that patients who have undergone surgery have received more radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an ongoing discussion about the role of low-ionisation radiation and the risk for cancer in CHD patients. 10 , 11 , 29 Unfortunately, in this study, we had no data describing the amount of radiation to which the patients were exposed. One can argue that it is likely that patients who have undergone surgery have received more radiation.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 9 In our recent report, we found that the overall risk of cancer in children and young adult patients with CHD in Sweden was more than twice as high as that of matched controls without CHD, 7 similar to previous studies. 8 , 9 The cause of this association is likely multifactorial, and radiation exposure 9 , 10 , 11 and underlying syndromes 12 , 13 may be possible factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of 11 270 children who received cardiac catheterisations in the UK [22] found an increased incidence of cancer, although this appeared to be largely associated with transplantation, rather than radiation exposure. Another recent study [19] reported 16 incident cases versus 3.64 expected among a cohort of 2770 German children exposed below age one year. All the above studies featured relatively small sample sizes, limiting power to detect excess risks at low doses.…”
Section: Introductionmentioning
confidence: 94%
“…Several epidemiological studies have been conducted to assess the risk of cancer in children exposed to radiation during cardiac catheterization procedures [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], yielding conflicting and inconclusive results ( Table 3 ).…”
Section: Radiation Exposure and Cancer Risk In Chdmentioning
confidence: 99%